2017
DOI: 10.2146/ajhp160964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pharmacist-driven methicillin-resistantStaphylococcus aureussurveillance protocol

Abstract: Among patients with suspected or confirmed pneumonia or an AECOPD, the expansion of pharmacists' traditional scope of practice to include a surveillance protocol using a MRSA PCR nares assay to guide vancomycin de-escalation resulted in a reduction in vancomycin utilization without compromising clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 26 publications
2
48
2
Order By: Relevance
“…Willis et al evaluated a pharmacist-driven protocol that resulted in a reduction of 1.8 days of anti-MRSA therapy, despite a protocol compliance rate of only 55%. 9,10 In our study, the patients in the MRSA PCR group appeared to be significantly more ill than those in the no MRSA PCR group, which may be the reason for the incongruences in our results compared to the current literature. Characteristics such as ICU admissions, positive chest radiographs, sepsis cases, pulmonary consults, and carbapenem usageall of which are indicative of a sicker population-were more prevalent in the MRSA PCR group.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Willis et al evaluated a pharmacist-driven protocol that resulted in a reduction of 1.8 days of anti-MRSA therapy, despite a protocol compliance rate of only 55%. 9,10 In our study, the patients in the MRSA PCR group appeared to be significantly more ill than those in the no MRSA PCR group, which may be the reason for the incongruences in our results compared to the current literature. Characteristics such as ICU admissions, positive chest radiographs, sepsis cases, pulmonary consults, and carbapenem usageall of which are indicative of a sicker population-were more prevalent in the MRSA PCR group.…”
Section: Discussioncontrasting
confidence: 89%
“…After isolating the MRSA PCR patients in the subgroup analysis, anti-MRSA DOT was 1.5 days shorter when the test was appropriately utilized, which is more comparable to what has been reported in the literature. 9,10 Only 60.6% of the MRSA PCR patients had their anti-MRSA therapy appropriately managed based on the MRSA PCR. Interestingly, a majority of patients in the inappropriate utilization group had MRSA PCR tests ordered more than 48 hours after beginning anti-MRSA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The overuse of anti-MRSA antibiotics has been associated with increased antibiotic resistance, nephrotoxicity, and increased healthcare costs and should be de-escalated once negative culture results are obtained [11]. Much like previous research, a pharmacy-driven protocol utilizing an MRSA nasal swab PCR in those suspected of having MRSA pneumonia resulted in a shorter duration of vancomycin therapy without increasing adverse events [11][12]. One could postulate that by decreasing the number of days a patient is on vancomycin for MRSA coverage in pneumonia that total healthcare costs would also be decreased because of fewer days in the hospital and less serum vancomycin levels being obtained.…”
Section: Discussionmentioning
confidence: 97%
“…Baby et al 12 highlighted a 46.6-hour reduction in the mean duration of anti-MRSA therapy (vancomycin or linezolid) for patients who primarily had hospitalacquired pneumonia. Willis et al 13 showed a similar reduction in the duration of vancomycin therapy (by w50 hours) in patients who received empirical vancomycin for suspected pneumonia and exacerbation of acute chronic obstructive pulmonary disease. In two of these previous studies, 12,13 pharmacists were permitted to independently order the MRSA screening test when receiving orders for anti-MRSA antibiotic drug therapy in patients with suspected pneumonia.…”
Section: Ethicillin-resistantmentioning
confidence: 84%
“…Willis et al 13 showed a similar reduction in the duration of vancomycin therapy (by w50 hours) in patients who received empirical vancomycin for suspected pneumonia and exacerbation of acute chronic obstructive pulmonary disease. In two of these previous studies, 12,13 pharmacists were permitted to independently order the MRSA screening test when receiving orders for anti-MRSA antibiotic drug therapy in patients with suspected pneumonia. This previous work effectively showed that pharmacistdriven protocols for ordering MRSA nasal PCR screening reduced the duration of vancomycin therapy by approximately 36 to 50 hours.…”
Section: Ethicillin-resistantmentioning
confidence: 84%